Beban Kognitif Siswa pada Materi Logaritma ditinjau dari Gaya Kognitif - Alifiani; Dea Fabila Arisandy (Universitas Swadaya Gunung Djati, 2025)
This study aims to identify the cognitive load experienced by tenth-grade students on the topic of logarithms, considering their cognitive styles, namely field dependent (FD) and field independent (FI). The research adopts a qualitative approach with a descriptive design. The participants of this study consist of 38 tenth-grade students from a high school in Malang, grouped based on their cognitive styles: FD and FI. Data were collected through a cognitive style questionnaire (HFT Test), logarithmic tests, and in-depth interviews. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that students with a field dependent cognitive style tend to experience high intrinsic cognitive load, particularly due to confusion in understanding the numerous concepts that need to be applied. In contrast, students with a field independent cognitive style experience extrinsic and germane cognitive loads, reflected in their difficulties in applying already-learned concepts. This study highlights the significant role of cognitive styles in influencing students' cognitive load when solving mathematical problems. Strengthening prerequisite knowledge and providing additional practice are recommended to reduce cognitive load, especially for students with a field dependent cognitive style.